Mechanisms of Injury-induced Axon Degeneration - Ding, Chen (Curr Opin Neurobiol, 2019)
Injury-induced axon degeneration in model organisms and cell culture has emerged as an area of growing interest due to its experimental tractability and to the promise of identifying conserved mechanisms that mediate axon loss in human disease. Injury-induced axon degeneration is also observed within the well-studied process of Wallerian degeneration, a complex phenomenon triggered by axon injury to peripheral nerves in mammals. Recent studies have led to the identification of key molecular components of injury-induced axon degeneration. Axon survival factors, such as NMNAT2, act to protect injured axons from degeneration. By contrast, factors such as SARM1, MAPK and PHR1 act to promote degeneration. The coordinated activity of these factors determines axon fate after injury. Since axon loss is an early feature of neurodegenerative diseases, it is possible that understanding the molecular mechanism of injury-induced degeneration will lead to new treatments for axon loss in neurodegenerative disease. Here we discuss the critical pathways for injury-induced axon degeneration across species with an emphasis on their interactions in an integrated signaling network.